Identification of Novel Variants of Thyroid Hormone Receptor Interaction Protein 13 That Cause Female Infertility Characterized by Zygotic Cleavage Failure - Hu, Huiling; Zhang, Shuoping; Guo, Jing; Meng, Fei; Chen, Xueqin; Gong, Fei; Lu, Guangxiu; Zheng, Wei; Lin, Ge (Frontiers in Physiology, 2022)
Zygotic cleavage failure (ZCF) is a severe, early type of embryonic arrest in which zygotes cannot complete the first cleavage. Although mutations in BTG4 and CHEK1 have been identified as genetic causes of ZCF, these genes only explain a small population of ZCF cases. Thus, the underlying genetic causes for other affected individuals need to be identified. Here, we identified three TRIP13 missense variants responsible for ZCF in two patients and showed that they followed a recessive inheritance pattern. All three variants resulted in obvious changes in hydrogen bonding and consistent increase in DNA damage. Additionally, transcriptomic sequencing of oocytes and arrested embryos containing these variants suggested a greater number of differentially expressed transcripts in germinal vesicle (GV) oocytes than in 1-cell embryos. Vital genes for energy metabolism and cell cycle procession were widely and markedly downregulated, while DNA repair-related genes were significantly upregulated in both GV oocytes and 1-cell embryos of patients. These findings highlight a critical role of TRIP13 in meiosis and mitosis, as well as expand the genetic and phenotypic spectra of TR1P13 variants with respect to female infertility, especially in relation to ZCF.